It’s all in the numbers: Cohesin stoichiometry - Matityahu, Avi; Onn, Itay (Frontiers in Molecular Biosciences, 2022)
Cohesin, a structural maintenance of chromosome (SMC) complex, organizes chromatin into three-dimensional structures by threading chromatin into loops and stabilizing long-range chromatin interactions. Four subunits in a 1:1:1:1 ratio compose the cohesin core, which is regulated by auxiliary factors that interact with or modify the core subunits. An ongoing debate about cohesin’s mechanism of action regards its stoichiometry. Namely, is cohesin activity mediated by a single complex or cooperation between several complexes that organize into dimers or oligomers? Several investigations that used various experimental approaches have tried to resolve this dispute. Some have convincingly demonstrated that the cohesin monomer is the active unit. However, others have revealed the formation of cohesin dimers and higher-order clusters on and off chromosomes. Elucidate the biological function of cohesin clusters and determining what regulates their formation are just two of the many new questions raised by these findings. We briefly review the history of the argument about cohesin stoichiometry and the central evidence for cohesin activity as a monomer vs. an oligomer. Finally, we discuss the possible biological significance of cohesin oligomerization and present open questions that remain to be answered.